Virtual Leadership: A Study in the IT Sector - Bárbara FERREIRA; Paulo PINTO-MOREIRA; Manuela LARGUINHO (Communications of International Proceedings, 2022)
The growing demands of organizational competitive advantage observed in the current scenario in a global and digital context, where people are increasingly physically distant, new and demanding challenges are posed to employees and companies. Particularly with regard to the development of teleworking activities and the respective virtual leadership (e-leadership). Therefore, the main objective of the present study is to analyze the perceptions of respondents regarding the leadership style of their leader teams in national and multinational companies, in the IT - Information Technology sector. From a sample consisting of 167 IT employees in a virtual work context, who answered the MLQ – Multifactor Leadership Questionnaire 5X MLQ by Avolio and Bass (2004), based on Full Range Leadership model, we analyze the perceptions of transformational, transactional, and laissez-faire leadership styles, with the results of leadership – extra-effort, effectiveness and satisfaction. From our results, it is possible to evidence that the more frequent the transformational leadership behaviors in the virtual teams, the higher the results achieved by the subordinates, on the other hand, the more frequent the laissez-leadership behaviors, the lower the results achieved by the team members. With this study, it was intended to contribute to the expansion of knowledge about leadership in a virtual context and, consequently, to a greater awareness about the demands of virtual contexts and the updating of practices by leaders.
Keywords: Virtual leadership; E-leadership; Leadership styles; IT Sector